Impact of hypoventilation training on muscle oxygenation, myoelectrical changes, systemic [K+], and repeated-sprint ability in basketball player - Lapointe, J.; Paradis-Deschênes, P.; Woorons, X.; Lemaître, F.; Billaut, F. (Frontiers in Sports and Active Living, 2020)
This study investigated the impact of repeated-sprint (RS) training with voluntary hypoventilation at low lung volume (VHL) on RS ability (RSA) and on performance in a 30-15 intermittent fitness test (30-15IFT). Over 4 weeks, 17 basketball players included eight sessions of straight-line running RS and RS with changes of direction into their usual training, performed either with normal breathing (CTL, n = 8) or with VHL (n = 9). Before and after the training, athletes completed a RSA test (12 × 30-m, 25-s rest) and a 30-15IFT. During the RSA test, the fastest sprint (RSAbest), time-based percentage decrement score (RSASdec), total electromyographic intensity (RMS), and spectrum frequency (MPF) of the biceps femoris and gastrocnemius muscles, and biceps femoris NIRS-derived oxygenation were assessed for every sprint. A capillary blood sample was also taken after the last sprint to analyse metabolic and ionic markers. Cohen's effect sizes (ES) were used to compare group differences. Compared with CTL, VHL did not clearly modify RSAbest, but likely lowered RSASdec (VHL: -24.5% vs. CTL: -5.9%, group difference: -19.8%, ES -0.44). VHL also lowered the maximal deoxygenation induced by sprints ([HHb]max; group difference: -2.9%, ES -0.72) and enhanced the reoxygenation during recovery periods ([HHb]min; group difference: -3.6%, ES -1.00). VHL increased RMS (group difference: 18.2%, ES 1.28) and maintained MPF toward higher frequencies (group difference: 9.8 ± 5.0%, ES 1.40). These changes were concomitant with a lower potassium (K+) concentration (group difference: -17.5%, ES -0.67), and the lowering in [K+] was largely correlated with RSASdec post-training in VHL only (r = 0.66, p < 0.05). However, VHL did not clearly alter PO2, hemoglobin, lactate and bicarbonate concentration and base excess. There was no difference between group velocity gains for the 30-15IFT (CTL: 6.9% vs. VHL: 7.5%, ES 0.07). These results indicate that RS training combined with VHL may improve RSA, which could be relevant to basketball player success. This gain may be attributed to greater muscle reoxygenation, enhanced muscle recruitment strategies, and improved K+ regulation to attenuate the development of muscle fatigue, especially in type-II muscle fibers.